Implementasi Peraturan Presiden Nomor 104 Tahun 2007 Tentang Penyediaan, Pendistribusian Dan Penetapan Harga Liquified Petroleum Gas Tabung 3 Kilogram - Suryanti, Neni; Rauf, Muhammad A (PATTIMURA Legal Journal, 2024)
Introduction: Kerosene to Liquified Petroleum Gas (LPG) conversion program as part of the Indonesian government's strategy to reduce kerosene subsidies and improve budget efficiency. Purposes of the Research: Analyze the imperfection of the implementation of the supply, distribution and pricing of liquified petroleum gas cylinders of 3 kilograms, especially related to price abuse by some business actors. Methods of the Research: The type of research in this paper is sociological legal research, which observes the characteristics of community behavior in a region in a certain aspect of social life. Results Originality of the Research: From the research results, three main points can be concluded. First, data analysis shows that there are still differences in the retail prices of 3 Kg LPG Gas, which exceed the Highest Retail Price (HET) set by the government. Furthermore, there are discrepancies in the distribution of 3 Kg LPG Gas to the poor, and sales to those who should not qualify. Despite regulations and sanctions, not all distributors comply with the rules. Second, inhibiting factors in the implementation of 3 Kg LPG Gas sales in Hutaraja Tinggi District, Padang Lawas Regency, involve limitations in human resources, lack of participation from the surrounding community, weak sanctions from the Department of Cooperatives, SMEs, Industry, and Trade of Padang Lawas Regency, lack of awareness from agents and officers, as well as infrastructure problems. Third, efforts that can be made by the Department of Cooperatives, SMEs, Industry, and Trade include coordination with relevant parties, such as distributors, retailers, and LPG gas agents, to ensure smooth distribution. Efforts to collaborate with relevant parties are expected to accelerate the distribution process and address potential obstacles in the field. Additionally, the department can monitor the stock of 3 kg LPG gas in the Hutaraja Tinggi District and monitor the distribution route to ensure the availability of gas evenly. Outreach and education programs for the community are also proposed to ensure the safe and efficient use of LPG gas. Supervision of prices and availability of LPG gas, opening of complaint channels for the public, and the use of information technology are also included in the proposed efforts. Furthermore, the department is expected to collaborate with private parties, including local traders or entrepreneurs, to support the distribution of LPG gas in the area.